The Exocrine Pancreas in Cystic Fibrosis in the Era of CFTR Modulation: A Mini Review - McKay, Isabelle R.; Ooi, Chee Y. (Frontiers in Pediatrics, 2022)
Cystic fibrosis (CF) is a common disorder of autosomal recessive inheritance, that once conferred a life expectancy of only a few months. Over recent years, significant advances have been made to CF therapeutic approaches, changing the face of the disease, and facilitating the partial restoration of pancreatic function. This mini review summarizes the current landscape of exocrine pancreatic management in CF and explores areas for future direction and development.